Amidst Covid-19 Pandemic: An Adaptive Disaster Governance in Yogyakarta, Indonesia - Hizbaron, Dyah Rahmawati; Ruslanjari, Dina; Mardiatno, Djati (Social sciences (Basel), 2021)
Since Indonesia reported its first case of COVID-19 in the capital, Jakarta, in early March of 2020, the pandemic has affected 102,051,000 lives. In the second week of the month, the government mandated all sectors to take necessary actions to curb the spread. The research set out to evaluate how the disaster emergency response was carried out amid the COVID-19 pandemic in the Special Region of Yogyakarta (SRY). The research employs qualitative observation of adaptive governance variables, i.e., infrastructure availability, information, conflict mechanism, regulation, and adaptation. The research analyzed primary data collected from focus group discussions with key persons at the Local Disaster Management Agency, Local Development Planning Agency, and Disaster Risk Reduction Platform responsible for the crisis and included an online survey to validate data. The research revealed that the SRY had exhibited adaptive governance to the COVID-19 pandemic, as apparent by, among others, open-access spatial and non-spatial data, extensive combined uses of both types of data, and prompt active engagement of communities in the enforcement of new rules and regulations mandated by national and provincial governments. Furthermore, during emergency responses to COVID-19, the stakeholders provided infrastructure and information, dealt with conflicts in multiple spatial units, encouraged adaptations, and formulated emergent rules and regulations. For further research, we encourage qualitative analysis to confront other types of natural disaster for the research area.